Descriptive Analysis of Undergraduate Community Medicine Question Papers and Blueprint Preparation: A Study from West Bengal - Sukesh Das; Abhishek Ingole; Santanu Ghosh; Samir Dasgupta (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Periodic review of Question papers is needed to ensure validity of student assessment. Blueprint is an effective tool to guide Paper setters. Objectives: To assess coverage and weightage of content areas in last 10 years (2012-2021) UG Community Medicine Question papers in West Bengal and to prepare a Blueprint of teaching and assessment in Theory Examination for the above subject. Method: Secondary data analysis was done on University Question papers (40 in number). For Blueprinting, inputs of 13 Faculty members were considered. The duration of the study was one year (Nov 2021-Oct 2022). Results: Overall, Basic and Disease Epidemiology were given maximum weightage (10.2%+23.8%= 34.0%) followed by Maternal and child health (MCH) (14.2%). Poor coverage and weightage was seen in Social & Behavioural sciences, Health planning and management, Geriatric health problems and Genetic diseases, which were allotted only 4.2% marks combined. There was cross-over of topics between two Papers (averaging 4.3% to Paper I and 8.4% to Paper II) in all the years with wide range across the period (2012 - 2021). The Blueprint suggested decrease in weightage of Epidemiology (28.4% vs 34.0%) and Health care delivery (5.0% vs 7.8%) whereas increase of weightage of 'Others' (24.2% vs 14.8%) compared to Question papers. Conclusion: There was inconsistency in coverage and weightage to different topics across the years. This review, along with the Blueprint prepared, would be helpful to improve teaching and assessment in the above subject.